Original paperThe role of trkB receptor in the formation of post-traumatic neuroma - Kotulska, Katarzyna; Larysz-Brysz, Magdalena; Marcol, Wiesław; Grajkowska, Wiesława; Jóźwiak, Sergiusz; Lewin-Kowalik, Joanna (Folia Neuropathologica, 2006)
The outcome of peripheral nerve injury is often impaired by post-traumatic neuroma developing at the injury site. Neuroma is usually accompanied by neuropathic pain, which is usually resistant to most analgesics and presents a serious clinical problem. The mechanisms underlying post-traumatic neuroma remain unclear, but they are likely associated with regeneration processes. Brain-derived neurotrophic factor (BDNF) and its receptor, trkB, are strongly implicated in axonal regeneration after injury. The aim of this work was to examine the role of trkB in post-traumatic neuroma formation. The sciatic nerve was transected in wild-type and heterozygous trkB-deficient mice. The nerve was either left cut or immediately sewn up or the gap injury model was performed. The gap was provided with an autologous or cross (obtained from another genetic group) graft. Sixteen weeks after surgery, the animals were sacrificed and histologic evaluations were performed. We found very limited or no neuroma formation in wild-type animals, regardless of the surgical procedure. In the majority of trkB-deficient mice, the post-traumatic neuroma was found at the end of the proximal stump of the transected nerve. In the gap injury model, in trkB-deficient animals receiving wild-type graft, there was no neuroma at the join site between the graft and distal stump of the nerve. In contrast, if the graft was autologous, neuroma formed at both joints. We also noticed many more mast cells accumulated at the surgery site in trkB-deficient than in wild-type animals. These results indicate the important role of BDNF receptor in post-traumatic neuroma formation.